Characterization of dehydrated okara - Botor, Adolfo B.
ABSTRACT The nutritional content and functional properties of dehydrated okara were evaluated in the study. A shelf stability test was also conducted through monitoring the microbiological and physico-chemical properties of dehydrated okara packed in low density polyethylene bags (LDPE) and stored at room and refrigerated temperatures for a month. The time taken to completely dehydrate okara using a cabinet dryer was found to be approximately 4 hours at 60°C. Dehydrated okara obtained a low yield of 13.76% due to its high moisture content (87.50% wet basis). Except for carbohydrates and crude fiber, it has lower proximate compositions as compared to soy flour. In terms of functionality, dehydrated okara was found to have high water absorption capacity, high solubility outside the pH range of 2-4, good fat absorption, gelling and emulsifying capacities and also had the ability to form films. Based on these results, okara can be a possible functional ingredient in food formulations such as in meat systems. Microbiological evaluation showed that the TPC and YMC of dehydrated okara packed in LDPE bags generally increased with storage time for both temperatures. Physico-chemical tests showed that dehydrated okara stored at room temperature is not significantly different (p<0.05) with that stored at refrigerated temperature. No significant difference was also observed as the weeks progressed (p<0.05) for the pH, water activity and lightness in color (l* value) of dehydrated okara. However, there was a significant difference (p<0.05) for the a* and b* color values per week. It is recommended to conduct an accelerated shelf life study that would determine the approximate shelf life of dehydrated okara.